Experiential training with Lego® for students of Primary Educational Sciences - Luisa Salmaso (Firenze University Press, 2019)
This paper presents the assumptions and the outcomes of perceived efficacy of a workshop experience carried out with LEGO®. It involved 25 university students of Primary Education, during their internship training course.   Workshop formativo esperienziale con il Lego® per studenti e studentesse di Scienze della Formazione Primaria. Questo articolo presenta gli assunti e gli esiti di efficacia formativa percepita riguardanti un'esperienza di workshop con i LEGO® svolta con 25 studenti di Scienze della Formazione Primaria, durante il loro percorso di tirocinio indiretto.